A review on reducing indoor particulate matter concentrations from personal‐level air filtration intervention under real‐world exposure situations. (10th August 2021) - Zhu, Yutong; Song, Xiaoming; Wu, Rongshan; Fang, Jiakun; Liu, Lingyan; Wang, Tong; Liu, Shuo; Xu, Hongbing; Huang, Wei
Abstract: Improving air quality in indoor environments where people live is of importance to protect human health. In this systematic review, we assessed the effectiveness of personal‐level use of air filtration units in reducing indoor particulate matters (PM) concentrations under real‐world situations following systematic review guidelines. A total of 54 articles were included in the review, in which 20 randomized controlled/crossover trials that reported the changes in indoor fine PM (PM2.5 ) concentrations were quantitatively assessed in meta‐analysis. Standardized mean differences (SMDs) were calculated for changes in indoor PM concentrations following air filtration interventions. Moderate‐to‐large reductions of 11%–82% in indoor PM2.5 concentrations were observed with SMD of −1.19 (95% CI: −1.50, −0.88). The reductions in indoor PM concentrations varied by geographical locations, filtration technology employed, indoor environmental characteristics, and air pollution sources. Most studies were graded with low‐to‐moderate risk of bias; however, the overall certainty of evidence for indoor PM concentration reductions was graded at very low level. Considering the effectiveness of indoor air filtration under practical uses, socio‐economic disparities across study populations, and costs of air filter replacement over time, our results highlight the importance of reducing air pollution exposure at the sources.